Fortitude Meets Perseverance: Unraveling the Link Between Hardiness, Grit, and Academic Burnout Among Architecture Students in Surabaya - Amelia, Syindi Rosa; Asiyah, Siti Nur; Anto, Abdul Haris Fitri (Universitas Negeri Semarang, 2024)
The increasing prevalence of academic burnout among university students in Indonesia necessitates a deeper understanding of its associated factors. This study aims to examine the relationship between hardiness, grit, and academic burnout among architecture students in Surabaya. Utilizing a quantitative correlational approach, the research involved 245 architecture students enrolled in public universities across Surabaya, selected through disproportionate stratified random sampling. The Maslach Burnout Inventory-Student Survey (MBI-SS) was employed to measure academic burnout, while hardiness was assessed using the Dispositional Resilience Scale (DRS-15-Revised), and grit was measured through Angela Duckworth’s Grit Scale (2009). The findings indicate that hardiness and grit are simultaneously negatively associated with academic burnout. The regression analysis revealed a negative coefficient, suggesting that higher levels of hardiness and grit are associated with lower levels of academic burnout.